Abject Objects: Perversion and the Modernist Grid. Issue 3 (1st October 2020) - Proto, Francesco
Abstract: This article challenges current psychoanalytical thought according to which the three Lacanian clinics of the neurotic, pervert and psychotic coexist in any given era, and suggests instead that identifiable environmental conditions are key to the surfacing of a specific and dominant construction of the self. In the case of the pervert, the narcissistic wounds inflicted by science and technology, as well as an increasingly hostile lifestyle dictated by the Industrial Revolution, become key factors that delineate a form of subjectivity in urgent need of overcoming internal splits. The modernist grid, which both the artistic avant-garde and the pioneers of modern architecture address during the first half of the twentieth century as the panacea for a corrupted world, is here discussed in terms of a subject whose imaginary worldview is determined by the vantage point offered by visual-machines, such as geometric grids, as applied to the production of a sanitized and overcontrolled urban environment. Both the mechanisms and outcomes of this interpretation of the evolution of Western city design are part of the original research question that this article addresses.